2022
DOI: 10.3390/polym14071370
|View full text |Cite
|
Sign up to set email alerts
|

Tri-Layered Vascular Grafts Guide Vascular Cells’ Native-like Arrangement

Abstract: Bionic grafts hold great promise for directing tissue regeneration. In vascular tissue engineering, although a large number of synthetic grafts have been constructed, these substitutes only partially recapitulated the tri-layered structure of native arteries. Synthetic polymers such as poly(l-lactide-co-ε-caprolactone) (PLCL) possess good biocompatibility, controllable degradation, remarkable processability, and sufficient mechanical strength. These properties of PLCL show great promise for fabricating synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Overall, all the fibers were connected without any beads or gross defects. The different arrangements of the fibers likely provided different physical, mechanical, and biocompatibility properties ( Dehghan and Khajeh Mehrizi, 2022 ; Ozdemir et al, 2022 ; Yuan et al, 2022 ). The subsequent experiments were conducted with random- and oriented-fiber membranes, and it was expected that the oriented-fiber membranes would be more helpful to the growth and proliferation of cells and promote the regeneration of new tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, all the fibers were connected without any beads or gross defects. The different arrangements of the fibers likely provided different physical, mechanical, and biocompatibility properties ( Dehghan and Khajeh Mehrizi, 2022 ; Ozdemir et al, 2022 ; Yuan et al, 2022 ). The subsequent experiments were conducted with random- and oriented-fiber membranes, and it was expected that the oriented-fiber membranes would be more helpful to the growth and proliferation of cells and promote the regeneration of new tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Electrospinning is an emerging technology used in tissue engineering ( Shi et al, 2022 ). The manufacturing methods of electrospinning are readily adjustable and can provide cell-specific surface structures of the membranes, it has been used in several studies to guide cell arrangement ( Yuan et al, 2022 ). The results herein demonstrated that electrospun rGO/PLCL membranes effectively guided cell arrangement with excellent physicochemical properties and cell compatibility.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Yuan et al created prostheses in which inner, middle, and outer layers were produced by ink printing, wet spinning, and electrospinning, respectively. The authors claimed that only the combined use of the 3 methods allowed for the production of prostheses with the desired wall thickness and mechanical properties [31]. By combining E-jet 3D printing and electrospinning methods, Huang et al produced tri-layered prostheses, which exhibited better mechanical properties in comparison to electrospun monolayer grafts [30].…”
Section: Discussionmentioning
confidence: 99%